Studying the structure and properties of quasi high-entropy alloys of the Fe-Co-Cr-Ni-Mn-Nb system with Mo additives - Kvon, Sv.S.; Kulikov, V.Yu.; Issagulov, A.Z.; Arinova, Saniya; Abildina , A.R. (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
The paper presents the results of studying the structure, hardness and wear resistance of quasi high-entropy alloys of the Fe-Co-Cr-Ni-Mn-Nb system with Mo additives. As a result of the study, it was shown that quasi high-entropy alloys of the Fe-Cr-Mn-Ni-Co-Nb system smelted with partial use of ferroalloys and additionally alloyed with Mo in the amount of 5-15% by weight, demonstrated very system alloys without Mo additives. The structure of the studied samples is represented by a mixture of solid solutions of Mn, Fe, Co, Ni of the face-centered cubic typе (FCC), Nb and Mo of the body centered cubic type (BCC), as well as interstitial phases: a carbide phase, a Laves phase and a σ-phase.